Волк насторожился: роман / Александр Бушков - Бушков Александр Александрович (Русский проект, 2002)
Экземпляры: ф.6 (20171214) / Инвентарный номер: 2195 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Б 90 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44